Choice of Mastectomy May Increase the Extent of Axillary Surgery in Women with Breast Cancer. Issue 11 (November 2022) - Zaveri, Shruti; Romanoff, Anya; Hirt, Leeza; Thompson, Lauren; Pisapati, Kereeti V.; Weltz, Christina; Schmidt, Hank; Port, Elisa
Introduction: Based on the ACOSOG Z0011 trial, women who undergo breast conservation therapy (BCT) and have limited disease in the axilla on sentinel lymph node (SLN) biopsy do not require axillary lymph node dissection (ALND). In this study we investigate the incidence of ALND in patients undergoing elective mastectomy with limited disease in the axilla to identify how many women may have been spared additional axillary surgery if they chose BCT. Methods: All women with invasive breast cancer treated at a single tertiary care breast center from 2010-2018 who were candidates for BCT but elected mastectomy and underwent SLN biopsy were identified through retrospective review of a prospectively maintained database. The primary outcome of interest was the incidence of ALND in women found to have a limited burden of disease in the axilla (1-2 positive SLNs). Results: The study population comprised 151 patients with invasive breast cancer eligible for BCT who chose mastectomy. On final pathology, 34 patients had 1-2 positive SLNs, and 16 of these patients underwent completion ALND. These 16 patients out of 151 overall lumpectomy candidates electing mastectomy (10.6%) could have been spared ALND if they did not elect mastectomy. Discussion: BCT candidates electing mastectomy have a 10.6% chance of undergoing more extensive axillary surgery than would have been recommended with BCT alone. The increased risk of undergoing additional axillary surgery should be incorporated into the preoperative discussion for patients choosing between BCT and mastectomy.